Evaluation of potentially toxic elements and microplastics in the water treatment facility - Bhat, Mansoor Ahmad; Janaszek, Agata (Environmental monitoring and assessment, 2024)
The potentially harmful effects of consuming potentially toxic elements (PTEs) and microplastics (MPs) regularly via drinking water are a significant cause for worry. This study investigated PTEs (Cd, Cu, Cr, Ni, Pd, Zn, Co), MPs, turbidity, pH, conductivity, and health risk assessment in the water treatment plant in Kielce, Poland. Zn had the highest concentrations throughout the water treatment facility, whereas Cd, Pb, and Co had lower concentrations (< 0.1 µg/L). The order of the concentrations among the specified PTEs was like Zn˃Cu˃Ni˃Cr˃Cd˃Pb and Co. The minimum turbidity was 0.34, and the maximum was 1.9 NTU. The range of pH in water samples was 6.51—7.47. The conductivity was 1,203—1,445 ms in water samples. These identified MPs were categorized into fiber and fragments. The color of these identified MPs was blue, red, black, green, and transparent. The minimum and maximum size of the MPs was 196 and 4,018 µm, while the average size was 2,751 ± 1,905 µm. The average concentration of MPs per liter of the water treatment plant was 108.88 ± 55.61. The elements listed are C, O, Na, Mg, Al, Si, K, Ca, and Ti. Fe and Zn were the predominant elements seen using EDX. HQ values of the PTEs were less than one for adults and children. The human health risk associated with all detected PTEs revealed that the HQ values exhibit a satisfactory degree of non-carcinogenic adverse health risk. HI values for adults and children age groups were less than one. In most water treatment samples, the carcinogenic value exceeds the threshold value of 10 −6 . The PTEs and MP concentrations in drinking water should be periodically monitored to minimize consumers' environmental pollution and health risks.